THE LIKELIHOOD OF DEVELOPING HYPOGLYCAEMIC STATES MAY BE AN INDIVIDUAL RISK FACTOR IN ELITE CANOEISTS - Makarova G.A.; Pogrebnoy A.I.; Chernukha S.M.; Karpov A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study aims to establish the significance of possible hypoglycemia in a complex of risk factors that have a negative impact on the functional state of the body of highly qualified athletes involved in canoeing and kayaking. Methods and structure of the study. This study analyzes scientific publications proving the importance of maintaining adequate carbohydrate reserves during intense physical activity. The study monitored venous blood glucose levels in elite canoeists. 73 male rowers (age range 18-37 years) of various skill levels (18 HMS, 21 MSIC, 34 MS) were examined 40 hours after the end of the last workout. Blood samples were taken and analyzed again in 35 people. Venous blood samples were analyzed at the Consultative and Diagnostic Center of the Research Institute – Regional Clinical Hospital No. 1 named after S.V. Ochapovsky (Krasnodar). A total of 166 measurements were taken. Results and conclusions. The centile levels of hematocrit were determined, and significant differences in glucose concentrations corresponding to hematocrit values ​​above and below the 75th centile were revealed. The study of the glucose level in venous blood 40 hours after the end of the workout demonstrated that the maximum values ​​(95th centile) were below the upper limits recommended by WHO for healthy people (5.5 mmol/l). At the same time, in 28.4% of cases, the blood glucose level was below 4.1 mmol/l, and in 52.0% of them it was below 3.9 mmol/l. In the context of sports medicine, it is advisable to introduce the concept of "potential hypoglycemia", which can be an individual risk factor affecting not only the effectiveness of training, but also contributing to the development of various clinical signs of non-functional overexertion, including risks for the cardiovascular system. In order to prevent potential hypoglycemia syndrome in athletes, it is imperative to add blood glucose level determination to the list of indicators monitored during ongoing medical and biological monitoring.